Genome-based approach to evaluate the metabolic potentials and exopolysaccharides production of Bacillus paralicheniformis CamBx3 isolated from a Chilean hot spring - Narsing Rao, Manik Prabhu; Singh, Ram Nageena; Sani, Rajesh K.; Banerjee, Aparna (Frontiers in Microbiology, 2024)
In the present study, a thermophilic strain designated CamBx3 was isolated from the Campanario hot spring, Chile. Based on 16S rRNA gene sequence, phylogenomic, and average nucleotide identity analysis the strain CamBx3 was identified as Bacillus paralicheniformis. Genome analysis of B. paralicheniformis CamBx3 revealed the presence of genes related to heat tolerance, exopolysaccharides (EPS), dissimilatory nitrate reduction, and assimilatory sulfate reduction. The pangenome analysis of strain CamBx3 with eight Bacillus spp. resulted in 24065 gene clusters, including 104 core genes, 7219 shell genes, and 16742 cloud genes. The EPS produced by B. paralicheniformis CamBx3 was extracted, partially purified, and evaluated for its functional activities. B. paralicheniformis CamBx3 EPS with concentration 5 mg mL-1 showed an optimum 92 mM ferrous equivalent FRAP activity, while the same concentration showed a maximum 91% of Fe2+ chelating activity. B. paralicheniformis CamBx3 EPS (0.2 mg mL-1) demonstrated β-glucosidase inhibition. The EPS formed a viscoelastic gel at 45°C with a maximum instantaneous viscosity of 315 Pa.s at acidic pH 5. The present study suggests that B. paralicheniformis CamBx3 could be a valuable resource for biopolymers and bioactive molecules for industrial applications.